The impact of adult diet on parasitoid reproductive performance - Benelli, Giovanni; Giunti, Giulia; Tena, Alejandro; Desneux, Nicolas; Caselli, Alice; Canale, Angelo (2018)
Diet is one of the most common influences on parasitoid reproductive traits. The life span, mating ability, fecundity, fertility and sex ratio of parasitoids can be affected by the quality of the adult diet. In the field, parasitoids can rely on different hosts and non-host nutrient sources, such as floral and extrafloral nectar, hemipteran honeydew and pollen, and various artificial diets have been used in mass rearing. In addition, some parasitoid species obtain nutrients by feeding on their host while adult (host feeding). In this review, we summarize current knowledge on the impact of the adult diet on the reproductive behavior of hymenopteran and dipteran parasitoids, with a particular focus on longevity, offspring production and host searching traits. First, we focus on food preferences and learning abilities of parasitoids to discriminate high-quality diets. Second, we analyze the impact of the adult diet on longevity, examining different natural and artificial food sources as well as the effect of their concentration and frequency. Third, we highlight the impact of the adult diet on host foraging. Fourth, we review the impact of adult diet on parasitoid offspring with special reference to (1) egg load, maturation and resorption, (2) parasitism and (3) progeny production and sex ratio. Finally, a number of implications for biological control and integrated pest management are discussed.